Chemical variables - lake from Almbergasjön, limnic profile, 2017-06-26–2024-01-11 - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2026)
Manual grab samples for chemical analysis are taken from the lake on a biweekly basis during ice-free conditions, and on a monthly basis during ice cover conditions. At the central lake sampling location water samples are collected from both epi- and hypolimnion during periods of stratification.
Abisko Scientific Research Station (2026). Chemical variables - lake from Almbergasjön, limnic profile, 2017-06-26–2024-01-11 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/b-PoNRi36cE_DUAQGD7rkqlS
Keywords: Abisko Scientific Research Station; Lake; Time instant; Time instant; pH; pH; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrate-N; Nitrate-N; Chlorine; Chlorine; Sulphate-S; Sulphate-S; Bromine; Bromine; Lithium; Lithium; Beryllium; Beryllium; Boron; Boron; Sodium; Sodium; Magnesium; Magnesium; Aluminium; Aluminium; Silicon; Silicon; Phosphorus; Phosphorus; Sulfur; Sulfur; Potassium; Potassium; Calcium; Calcium; Vanadium; Vanadium; Chromium; Chromium; Manganese; Manganese; Iron; Iron; Cobalt; Cobalt; Nickel; Nickel; Copper; Copper; Zinc; Zinc; Gallium; Gallium; Arsenic; Arsenic; Selenium; Selenium; Rubidium; Rubidium; Cadmium; Cadmium; Tellurium; Tellurium; Caesium; Caesium; Barium; Barium; Thallium; Thallium; Lead; Lead; Bismuth; Bismuth; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap